Inverted structure hybrid solar cells using CdS thin films - Yavuz, Nursel; Yuksel, Sureyya Aydin; Karsli, Adem; Gunes, Serap (ELSEVIER, 2013)
The photovoltaic performance of inverted structure hybrid solar cells fabricated using cadmium sulfide (CdS) films and the photoactive layer of P3HT (poly(3-hexyl)thiophene) and PCBM ([6,6]-phenyl C-61 butyric acid methyl ester) is reported. CdS thin films with different thicknesses were deposited using the spray deposition technique. Current voltage (I-V) characteristics were performed under dark and AM 1.5 illumination (mW/cm(2)) conditions. Inverted structure hybrid solar cells employing CdS thin films yield a short circuit current density of 1.9 mA/cm(2), resulting in a power conversion efficiency of ca. 0.3%. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Inverted structure solar cells; CdS thin films; Polymer solar cells; POLYMER PHOTOVOLTAIC CELLS; SPRAY-PYROLYSIS; TITANIUM-OXIDE; BENZOTHIADIAZOLE; THIOPHENE; Energy & Fuels; Materials Science; Physics